2009
DOI: 10.1016/j.bbamcr.2009.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Mixed lineage kinase 3 negatively regulates IKK activity and enhances etoposide-induced cell death

Abstract: Mixed Lineage Kinase 3 (MLK3) is a mitogen activated protein kinase kinase kinase (MAP3K) that activates multiple MAPK signaling pathways. Nuclear factor kappa B (NF-κB) is a transcription factor that has important functions in inflammation, immunity and cell survival. We found that silencing mlk3 expression with RNA interference (RNAi) in SKOV3 human ovarian cancer epithelial cells and NIH-3T3 murine fibroblasts led to a reduction in the level of the inhibitor of kappa B alpha (IκBα) protein. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As expected HFHC diet‐fed WT mice have increased JNK phosphorylation, which was reduced in the Mlk3 −/− mice on the same diet. MLK3 has been implicated in the activation of apoptotic cell death secondary to various stressful stimuli in neuronal, ovarian, pancreatic and hepatoma cells , on the other hand, hepatocytes depleted of MLK3 were partially protected from SFA‐induced apoptosis , a prominent feature of NASH . Consistent with the human disease, serum ALT and TUNEL‐positive liver cells were increased in mice fed the HFHC diet.…”
Section: Discussionmentioning
confidence: 75%
“…As expected HFHC diet‐fed WT mice have increased JNK phosphorylation, which was reduced in the Mlk3 −/− mice on the same diet. MLK3 has been implicated in the activation of apoptotic cell death secondary to various stressful stimuli in neuronal, ovarian, pancreatic and hepatoma cells , on the other hand, hepatocytes depleted of MLK3 were partially protected from SFA‐induced apoptosis , a prominent feature of NASH . Consistent with the human disease, serum ALT and TUNEL‐positive liver cells were increased in mice fed the HFHC diet.…”
Section: Discussionmentioning
confidence: 75%
“…Instead, we show that decreased JNK activation in Cdc42/Rac1 and MLK3 deficient cells correlates with attenuation of palmitate-induced cell death, suggesting a role for MLK3 in SFA-induced death in hepatocytes. Indeed, MLK3 has been shown to mediate JNK activation in some forms of stress-induced apoptosis [10, 16, 31, 48]. Interestingly, it was recently demonstrated that GSK-3 promotes JNK-dependent lipoapotosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PEA3 expression is also elevated in advanced metastatic ovarian cancer [36]. Some MMP genes are also transcriptionally activated by NF-3B; however, our previous studies indicate that MLK3 does not promote NF-κB activation, and therefore it is not likely a major contributor to MLK3-dependent activation of MMP gene expression [37]. …”
Section: Discussionmentioning
confidence: 99%